Household growth and demographic transition in Latin America: implications for the analysis of housing needs - García García, Diva Marcela (2025)
The advancement of demographic transition brings immediate changes that shape household growth. This article examines the evolution of this process in Latin American countries and its implications for housing policy. Using census data from 17 countries in the region, as well as Spain and Portugal, this study employs a decomposition method to analyze the demographic factors influencing recent household growth. The findings highlight the diminishing impact of population growth itself. Furthermore, it underscores the increasingly influential role of age structure and behavioral factors in household formation. Since it is less predictable and closely linked to socioeconomic conjunctures, this last determinant introduces elements of uncertainty. As a result, the article concludes that enhancing methods to incorporate these components and their cyclical and uncertain trajectories into modeling household growth is essential. It also emphasizes the need to adopt housing policy planning strategies for the post-transitional future, where uncertainties will prevail.